PENYULUHAN KESEHATAN DEMAM BERDARAH DENGUE DI MASA PANDEMI COVID-19 - Tan, Suriyani; Yuliana, Yuliana; Devita, Arleen; Machrumnizar, Machrumnizar (JUARA: Jurnal Wahana Abdimas Sejahtera, 2023)
Dengue Hemorrhagic Fever (DHF) is caused by the dengue virus and is still a public health problem today, especially in urban areas. The death rate caused by this disease is very high if not treated immediately. Dengue virus is mainly transmitted by female mosquitoes Aedes aegypty and Aedes. albopictus. Aedes spp mosquitoes are mosquitoes that have the ability to reproduce quickly because the eggs of these mosquitoes can live in dry conditions. Indonesia implements the Jumantik program (Larva Monitoring staff) as a way of eradicating mosquitoes. However, with the current implementation of PSBB (Large-Scale Social Restrictions) in DKI Jakarta, this program has become a bit difficult to implement. This counseling was carried out as part of increasing public literacy in understanding dengue fever from symptoms to prevention at the household level, so that people became aware of this disease even in the midst of the Covid-19 pandemic. The counseling was conducted online and prior to the counseling, an initial survey of understanding about DHF was conducted and a final survey was conducted after the counseling to assess the level of public understanding about DHF. The results achieved in the form of benefits, especially for the community, namely residents understand about dengue fever and its prevention through eradicating mosquito larvae in their respective homes, which in turn can reduce the number of dengue cases in Jakarta.